Alzheimer's disease: clinical update on epidemiology, pathophysiology and diagnosis. (August 2018) - Eratne, Dhamidhu; Loi, Samantha M; Farrand, Sarah; Kelso, Wendy; Velakoulis, Dennis; Looi, Jeffrey CL
Objectives: To provide a clinical update for general psychiatrists on the assessment and diagnosis of Alzheimer's disease (AD), highlighting current issues regarding epidemiology, risk factors and pathophysiology from recent relevant research findings. Conclusions: Psychiatrists can apply their skills and training in the diagnosis of AD, which is based upon a comprehensive assessment comprising history, investigations, and cognitive and functional assessment, guided by accepted diagnostic criteria.